2020
DOI: 10.1038/s41598-020-68322-6
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary paracoccidioidomycosis in AhR deficient hosts is severe and associated with defective Treg and Th22 responses

Abstract: AhR is a ligand-activated transcription factor that plays an important role in the innate and adaptive immune responses. In infection models, it has been associated with host responses that promote or inhibit disease progression. In pulmonary paracoccidioidomycosis, a primary fungal infection endemic in Latin America, immune protection is mediated by Th1/Th17 cells and disease severity with predominant Th2/Th9/Treg responses. Because of its important role at epithelial barriers, we evaluate the role of AhR in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 73 publications
(117 reference statements)
2
18
0
1
Order By: Relevance
“…CH223191 treatment reduced the number of IDO+ CD11c+ cells and increased the number of viable P. brasiliensis yeasts present in the lungs at both time points studied. This agrees with our previous reports demonstrating the increased P. brasiliensis growth when IDO is metabolically inhibited or genetically ablated, possibly by the increased TRP availability for fungal metabolism (34)(35)(36)(37), The reduction in IDO was concomitant with that of AhR, the two components that are mutually controlled (14). Contrasting the treatments with FICZ and L-Kyn, CH223191 caused a large increase in the number of CD11c+ myeloid cells expressing activation molecules, intracellular TNF-a and a preferential expansion of myeloid DCs.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…CH223191 treatment reduced the number of IDO+ CD11c+ cells and increased the number of viable P. brasiliensis yeasts present in the lungs at both time points studied. This agrees with our previous reports demonstrating the increased P. brasiliensis growth when IDO is metabolically inhibited or genetically ablated, possibly by the increased TRP availability for fungal metabolism (34)(35)(36)(37), The reduction in IDO was concomitant with that of AhR, the two components that are mutually controlled (14). Contrasting the treatments with FICZ and L-Kyn, CH223191 caused a large increase in the number of CD11c+ myeloid cells expressing activation molecules, intracellular TNF-a and a preferential expansion of myeloid DCs.…”
Section: Discussionsupporting
confidence: 93%
“…This transcription factor is expressed by epithelial and immune cells, is involved in mucous secretion (59) and the balanced immune response in the lung (49). In accordance, our studies have demonstrated the important participation of AhR in the control of disease severity and immune response in pulmonary PCM (34)(35)(36)(37)46). The present study allowed us to demonstrate that this fungal infection can be modulated by AhR ligands in opposed directions as previously demonstrated in other experimental models (10,11,45), suggesting their therapeutic use in different forms of the disease.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations